Intralesional hemorrhage in Krukenberg tumor: a case report and review of the literature - La Fianza, A. (Springer International Publishing AG, 2013)
Acute abdomen due to female genital apparatus disease is very rare. Most are due to intralesional effusion of benign tumors. The authors present a 40-year-old woman with acute abdomen pain due to haemorrhagic ovarian metastasis of colorectal cancer, focusing on the role of imaging to get the management of the patient.